Taxation of Investment and Savings in a World Economy - Gordon, Roger (American Economic Review, 1986)
The equilibrium of capital and equilibrium market prices are derived for a world economy with a unified securities market, mobile capital, no uncertainty, and varying tax rates on different sources of income in each country. The paper then characterizes optimal tax rates for a small country in this setting, focusing on the peculiar incentives created when the before-tax rate of return differs among securities due to differences in their typical tax treatment. Copyright 1986 by American Economic Association.